2014
DOI: 10.4103/0973-1075.132627
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in cancer patients undergoing chemotherapy in a tertiary care center in Malwa region of Punjab

Abstract: Objective:The objective of this prospective, non-interventional, 4-month observational study was to analyze and compare patient-reported quality of life (QOL) and their physical/psychosocial symptom burden during their respective chemotherapy sessions.Materials and Methods:A prospective and descriptive study was carried out jointly by Pharmacology and Oncology Departments of a tertiary care center in Malwa region of Punjab. The data collection was performed by administering validated questionnaire/response aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
2
26
1
5
Order By: Relevance
“…It is also possible that, as the chemotherapy session progressed, patients experienced better HRQoL following their psychological adjustment as the ability to cope with disease, treatment and effects of treatment would have been improved after completing several chemotherapy cycles. 30,31 Additionally, there was an increase in constipation after both ginger essential oil and FO interventions. The most likely explanation of the increase might be due to the common side effect of 5TH 3 anti-emetics.…”
Section: Discussionmentioning
confidence: 96%
“…It is also possible that, as the chemotherapy session progressed, patients experienced better HRQoL following their psychological adjustment as the ability to cope with disease, treatment and effects of treatment would have been improved after completing several chemotherapy cycles. 30,31 Additionally, there was an increase in constipation after both ginger essential oil and FO interventions. The most likely explanation of the increase might be due to the common side effect of 5TH 3 anti-emetics.…”
Section: Discussionmentioning
confidence: 96%
“…Finnish studies have shown that more than 90% of the total dietary intake of nutrient elements and potentially toxic metals comes from plant foods, spices and plant-derived beverages 12. Studies conducted by various reputable institutions have indicated that drinking water, particularly in the Malwa belt, can be a source of heavy metals, including fluoride and pesticides 2,3,13,14. This relatively high intake of contaminated food and water may explain the higher incidence and prevalence of cancer as found in the Malwa region of Punjab.…”
Section: Introductionmentioning
confidence: 99%
“…"Most of the patients needed counseling during the chemotherapy or radiotherapy sessions as they were found to be severely affected by anxiety and depression". Furthermore, the Biblical view of illness and human suffering was found to be closely related to the origin of sin and was a natural component of finite embodied human beings [15] . Enduring adversity could be used to display the work of God in a person's life and to facilitate the development of Christian character and spiritual growth [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Biblical view of illness and human suffering was found to be closely related to the origin of sin and was a natural component of finite embodied human beings [15] . Enduring adversity could be used to display the work of God in a person's life and to facilitate the development of Christian character and spiritual growth [15] . The eventual realization for most of the patients was that God is all-powerful and all-knowing, and he will reward those who do good unto Him [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation